CHARACTERISTICS OF MORPHOMETRIC PARAMETERS OF RAT TWISTED INTESTINE WALL IN SINGLE ADMINISTRATION OF CRYOPRESERVED PLACENTA AND ASEPTIC INFLAMMATION - Шепітько, К.В. (World of Medicine and Biology, 2014)
The experimental study has been carried out on 115 senior male rats. The comparative dynamics of morphometric parameters alterations of total wall thickness, thickness of mucosa, submucosa, muscular and serous coats ileum has been presented during a single administration of cryopreserved placenta and single administration of λ-carrageenan. Morphometric parameters of twisted intestine are not significantly different from the parameters of intact and control groups of animals. Single subcutaneous administration of cryopreserved placenta has an impact on studied morphometric parameters alterations, expressed in maximum increase in values at the 3rd day of the study and recovery to the values of intact group at the 30th day both during the comparison between the terms of study and group of intact animals. In aseptic inflammation of abdominal cavity a significant maximum increase in studied parameters has been revealed at the 3rd day of the study, indicating about the inflammatory process activity. At the 30th day of the experiment the parameters recovery to the level of intact group has been noted. The detected patterns of relationship are typical both during the experiment (as compared between the terms of the study) and for intact group of animals.